Among paradigms: Major ways of framing user-related problems in contemporary architectural discourse - Sirowy, Beata (FormAkademisk, 2012)
While a review of contemporary architectural theory indicates that user-related concerns have not been absent, this discussion remains rather fragmented and incidental. Seeking reasons behind this situation, this paper discusses the major paradigms underpinning contemporary architectural discourse and explicates how different paradigms ground different approaches to users. It reveals certain limitations of the dominating conceptual positions (positivism/postpositivism, critical theory, constructivism), and argues in turn for the relevance of phenomenology in supporting a more user- and context-sensitive architectural practice.